2012
DOI: 10.1021/ja305150c
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot in Situ Fabrication of Stable Nanocaterpillars Directly from Polyacetylene Diblock Copolymers Synthesized by Mild Ring-Opening Metathesis Polymerization

Abstract: We report a direct one-pot route for the preparation of supramolecules from simple polyacetylene diblock copolymers synthesized by mild ring-opening metathesis polymerization of cyclooctatetraene. This in situ nanoparticlization of conjugated polymer (INCP) approach is advantageous over conventional self-assembly processes because this method does not require any tedious postsynthetic treatments. Also, this direct approach provides intriguing supramolecules with a unique nanostructure resembling a caterpillar.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(123 citation statements)
references
References 32 publications
6
114
2
1
Order By: Relevance
“…Similar structures have been observed in experiments. [39][40][41] This type of structure obtained in our simulations is related to the stable interface formed by rigid nanocubes. The packing of the nanocubes on the surface of micelles slows down the surfactant exchange between micelles and the corresponding structure rearrangement; therefore the pearl-necklace-like structure can be stably formed as shown the movie in ESI.…”
Section: Simulation Results and Discussionsupporting
confidence: 59%
“…Similar structures have been observed in experiments. [39][40][41] This type of structure obtained in our simulations is related to the stable interface formed by rigid nanocubes. The packing of the nanocubes on the surface of micelles slows down the surfactant exchange between micelles and the corresponding structure rearrangement; therefore the pearl-necklace-like structure can be stably formed as shown the movie in ESI.…”
Section: Simulation Results and Discussionsupporting
confidence: 59%
“…A broad absorption peak with a maximum over 600 nm and an onset at 850 nm were clearly and consistently observed throughout the course of sonication. These observed wavelengths are among the highest reported for solution-synthesized PAs (26)(27)(28)(29), suggesting the formation of PA blocks with long conjugation lengths. The absorption peak continuously grew in intensity during the sonication process, indicating continuous formation of PA. After 120 min of sonication, the absorption maximum slightly shifted hypsochromically to 605 nm with a concomitant decrease in solubility and formation of particulates due to the relatively high content of insoluble PA. Long-wavelength absorption was observed even at the beginning of sonication, when the absorbance was still low ( fig.…”
mentioning
confidence: 70%
“…102 Moreover, studies of PFDMS BCPs with short corona -forming blocks showed that these materials yielded platelet micelles. 103 A wide range of crystallizable core-forming blocks other than PFDMS have now been employed to enable the formation of cylindrical/fiber-like micelles with crystalline cores and these include poly(3-hexylthiophene)), [104][105][106][107][108][109] poly(L-lactic acid) (PLLA), [110][111][112][113] polycaprolactone (PCL), 114,115 PEO, 116 PE, [117][118][119][120] poly(acrylonitrile), 121 poly(ferrocenyldimethylgermane) (PFDMG), 122 poly(ferrocenyldiethylsilane) (PFDES), 123 poly(ferrocenylmethylsilane)(PFMS), 124 PCL/PLLA, 125 poly(perfluoroethyloctylmethacrylate), 126,127 cholestorol-based polymers, 128 polyacetylene, 129,130 poly(pphenylene), 131 poly(3-heptylselenophene), 132 polyfluorene, [133][134][135] poly(pphenyleneethynylene), 136,137 poly(p-phenylenevinylene), [138][139][140][141][142] cyclic polypeptoids, 143 and poly(2-isopropyl-2-oxazoline).…”
Section: Influence Of Crystallization On Self-assembled Bcp Morphologiesmentioning
confidence: 99%